On the Negatively Subscripted Padovan and Perrin Matrix Sequences - Yilmaz, Nazmiye; Taskara, Necati (Communications in Mathematics and Applications, 2014)
The first main idea of this paper is to develop the matrix sequences that represent negatively subscripted Padovan and Perrin numbers. Then, by taking into account matrix properties for these new matrix sequences, some behaviours of negatively subscripted Padovan and Perrin numbers have been investigated. Moreover, we present the important relationships between negatively subscripted Padovan and Perrin matrix sequences.